2009
DOI: 10.1080/15402000903190207
|View full text |Cite
|
Sign up to set email alerts
|

Sleep as a Mediator in the Pathway From Violence-Induced Traumatic Stress to Poorer Health and Functioning: A Review of the Literature and Proposed Conceptual Model

Abstract: Millions of children are exposed to various forms of violence every year, resulting for many of them in psychological problems, decreased social functioning, and poorer overall quality of their relationships and lives. This article reviews the scientific literature investigating the role of sleep as a key mediator in the pathway between violence-induced traumatic stress and resulting negative health and behavioral outcomes. Based on evidence revealed by this review and general research on how exposure to viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 129 publications
(148 reference statements)
4
34
0
Order By: Relevance
“…While contrary evidence suggests that sleep problems prior to traumatic exposure place an individual at greater risk of developing PTSD after trauma exposure by reducing the body's capacity to cope with stress (Bryant, Creamer, O'Donnell, Silove, & McFarlane, 2010;Meerlo, Sgoifo, & Suchecki, 2008). Although evidence regarding which condition manifests first is mixed, further findings reveal that sleep problems in children played a critical mediating role between traumatic stress and negative psychological and social outcomes (Spilsbury, 2009), and one exploratory study found a 6 positive association between sleep disordered breathing and movements with suicidal behavior in a small group of female sexual assault victims with PTSD (Krakow et al, 2000).…”
Section: Introductionmentioning
confidence: 83%
“…While contrary evidence suggests that sleep problems prior to traumatic exposure place an individual at greater risk of developing PTSD after trauma exposure by reducing the body's capacity to cope with stress (Bryant, Creamer, O'Donnell, Silove, & McFarlane, 2010;Meerlo, Sgoifo, & Suchecki, 2008). Although evidence regarding which condition manifests first is mixed, further findings reveal that sleep problems in children played a critical mediating role between traumatic stress and negative psychological and social outcomes (Spilsbury, 2009), and one exploratory study found a 6 positive association between sleep disordered breathing and movements with suicidal behavior in a small group of female sexual assault victims with PTSD (Krakow et al, 2000).…”
Section: Introductionmentioning
confidence: 83%
“…For instance, a review of the literature concerning sleep as a mediator of the association between violence-induced trauma and poorer health found sleep to be a significant mediator for multiple outcomes, including immune dysfunction and depression, thus it is likely that this holds for associations between ACEs and poorer health [55]. Lee et al [22] found that a history of childhood abuse is statistically significantly associated with metabolic syndrome symptoms and diagnosis in adults: poor sleep quality explained 24% of the association between abuse and risk of metabolic syndrome diagnosis in women and 20% in men.…”
Section: Discussionmentioning
confidence: 99%
“…nightmares, sleep deprivation; (Germain, Buysse, & Nofzinger, 2008)). Stress from childhood abuse may also lead to poor sleep behaviors as coping mechanisms that may preclude sleeping soundly such as sleeping at irregular times and locations to avoid victimization (Spilsbury, 2009). In turn, a dysregulated sleep/wake cycle may lead to greater circulating levels of pro-inflammatory biomarkers that affect hemodynamics.…”
Section: Discussionmentioning
confidence: 99%